Carbonated hydroxyapatite‐assisted visible light degradation of methylene blue. Issue 1 (21st December 2021) - Asimeng, Bernard Owusu; Obeng, Ernest Emmanuel; Obeng‐Gyasi, Obed; Alipoormazandarani, Niloofar; Annan, Ebenezer; Nyankson, Emmanuel; Efavi, Johnson Kwame; Tiburu, Elvis Kwason; Foster, E. Johan; Czernuszka, Jan T.
Abstract: Carbonated hydroxyapatite (CHAp) material was prepared from calcite and phosphate‐containing solution using the wet chemical precipitation method. The CHAp material was used to remove methylene blue (MB) from simulated contaminated water and further degraded the MB with the help of visible light (VL). The structure of the CHAp was characterized using X‐ray diffractometry, infrared spectroscopy, Branuer–Emmett–Teller analysis, and scanning electron microscopy, while the energy bandgap, E g, reaction rate constant and MB removal/degradation efficiencies were studied using UV‐Vis spectroscopy. The characterization data revealed that the CHAp was a type‐B carbonate‐substituted hydroxyapatite material with a nonmicroporous network with an E g of 2.26–2.82 eV. The E g allowed VL entrapment that resulted in reactive free radicals that degraded the MBs in the CHAp. The reaction rate constant, K, and removal efficiencies, R, were modeled using the exponential decay function and descriptive statistics (DS), respectively. In close approximation, the K values of the reaction under VL were doubled when compared to the reaction under dark conditions. Under dark and under VL efficiencies, the DS showed a negative and zero skewness for MB removal by CHAp, respectively. The findings show that VL exposure on the CHAp causes a faster reaction rate constant and a higher MB removal efficiency within the time constraints, which would revolutionize dye removal from water industries in terms of cost‐effectiveness.